Turbulent flame speed in spark ignition engine combustion process using computational fluid dynamics - Muhammad Saiful, Mustafa (2011)
This thesis deals with the numerical study about turbulent flame speed in spark ignition engine during the combustion process using Computational Fluid Dynamics (CFD). The objective for this project is to analyze the behavior and predicted trend of turbulent flame speed that occurs during the combustion process at single operating point for 2000 revolution per minute (rpm) engine speed. Turbulent flame speed is the important parameter that controls the cylinder pressure during combustion process in spark ignition (SI) engine. This thesis described on technique to tackle the objective starting from engine modeling until finish of the project. The analysis is focusing on spark ignition combustion process of the baseline engine design, Mitsubishi magma 4G15. Engine was modeled using Solid work software and then analysis using CFD. The engine model was design in 3-Dimensional (3D). The speed of engine is fixed at single operating point at 2000 rpm. For numerical modeling approach, k-epsilon (k-) standard turbulence model was selected. The iteration number is set at 1500 iteration per time step. The accuracy test is based on cylinder pressure and the simulation data is validated with experiment data. It is known that an increase in turbulent flame speed increases the cylinder mixtures that have been burned. Thus increase the cylinder temperature and relates with the increase in cylinder pressure during the combustion process.